Mental health and co-existence with COVID-19: quality of life, fear, anxiety and burnout in the early endemic phase in Malaysia - Ooi, Pei Boon; Ho, Meng Chuan; Voon, Siok Ping; Lee, Kai Wei; Siang Ang, Austin Chin; Teng, Hui Jie; Pang, Khong Yun; Ching, Siew Mooi (Routledge, 2024)
After nearly three years of COVID-19 and multiple lockdowns, Malaysia entered the early endemic phase in April 2022. This transition brought new challenges and required continued adaptation, with mental health concerns rising due to the uncertainties of living with the virus. This study thus sought to examine, within the context of the early endemic phase, the quality of life among Malaysians, the mediating effect of fear arising from COVID-19, and how it results in anxiety and burnout. A cross-sectional online survey was conducted among 462 respondents (Mean age = 24.42; S.D.= 7.88), utilizing validated measures including the Malay versions of the COVID-19 Anxiety Scale, COVID-19 Burnout Scale, Fear of COVID-19 Scale, and the abbreviated WHO Quality of Life Scale. Results showed that quality of life negatively predicted an individual’s fear and burnout, but not anxiety. Fear arising from COVID-19 mediated the relationship between anxiety and burnout. While co-existing with COVID-19, it is important to consider the psychological impacts of this co-existence in promoting good health and individual well-being. Governments can use this data to implement risk management programs and policies to improve individuals’ quality of life. Post-pandemic, recognizing and addressing fear is essential for effective interventions.